2010
DOI: 10.3402/ljm.v5i0.4847
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO blood groups with diabetes mellitus

Abstract: ObjectiveSo far no studies have been performed in Malaysia to look at association of diabetes mellitus (DM) with blood groups. We studied the association of ABO blood groups with DM type 2.Patients and methodologyIt was a case control study conducted at Kepala Batas Hospital Batas, Penang, Malaysia in the year 2009, involving 70 patients with DM type 2 and 140 healthy controls. Ethical approval was obtained from Universiti Sains Malaysia. Blood samples were collected from the patients after consent. Samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 11 publications
7
47
2
1
Order By: Relevance
“…Wherever decreased association of blood group AB with diabetis mellitus found in study of Buckwalter, [13] Zhang et al [14] Our study has increased association of blood group O with DM. This results are similar with Karagoz et al, [9] Zhang et al, [14] and dissimilar with Kamil et al, [15] Fagherazzi et al [16] Bener and Yousafzai, [17] Qureshi and Bhati. [18] Our study has decreased association of diabetes with blood group B.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Wherever decreased association of blood group AB with diabetis mellitus found in study of Buckwalter, [13] Zhang et al [14] Our study has increased association of blood group O with DM. This results are similar with Karagoz et al, [9] Zhang et al, [14] and dissimilar with Kamil et al, [15] Fagherazzi et al [16] Bener and Yousafzai, [17] Qureshi and Bhati. [18] Our study has decreased association of diabetes with blood group B.…”
Section: Discussionsupporting
confidence: 90%
“…[18] Our study has decreased association of diabetes with blood group B. This finding is similar to Qi et al [19] but different from Kamil et al [15] and Bener and Yousafzai, [17] Joseph, [13] Hadeal and Ali, [20] Moinzadeh et al [21] The possible explanation of conflicting results regarding the association between ABO blood groups and DM could be racial and geographical variations playing role in the genetic expression of the disease.…”
Section: Discussionsupporting
confidence: 77%
“…23 Another study conducted by Muhammad K et al, 3 in their study of association of ABO blood groups with diabetes mellitus, they also showed that there was a negative association between ABO blood groups A and O with DM type 2, with A and O group having less chances of diabetes. 24 Several reports have evaluated the possible relationship between diabetes mellitus and Rh blood group; however, the populations vary and the findings are inconsistent. Study conducted by Jha S et al, 25 found no association between the ABO blood group and DM.…”
Section: Discussionmentioning
confidence: 99%
“…Aird et al reported such a relationship with gastric cancer. They found that blood group A was significantly (19). Qureshi and bhatti found that the frequency of the blood groups B and O was significantly higher and lower respectively in diabetic patients than in the general population (20).…”
Section: Discussionmentioning
confidence: 99%